Effect of aging treatment on the microstructure and mechanical properties of Al-3.02Mg-0.2Sc-0.1Zr alloy printed by selective laser melting. (15th April 2019) - Li, Ruidi; Chen, Hui; Zhu, Hongbin; Wang, Minbo; Chen, Chao; Yuan, Tiechui
Abstract: Additive manufacturing Al-Mg-Sc-Zr alloys offer significant advantages for lightweight application with complex shapes. The paper systematically investigated the effects of aging treatment on microstructural evolution and mechanical properties of SLM printed Al-3.02Mg-0.2Sc-0.1Zr alloy. The SLM printed sample with a relative density of 99.2% was achieved at an optimal laser parameters. After aging, the hardness was improved from initial 85 HV of as-printed sample to 120 HV. The strength and ductility trade-off of the printed sample can be tailored by regulating aging parameters; the maximal tensile strength of 400 MPa and yield strength of 327 MPa can be obtained at an optimal aging parameters. The XRD patterns show the secondary peak of Al3 (Sc, Zr) after aging treatment due to Al3 (Sc, Zr) particles separation from the α-Al matrix and the diffraction angles shifts to a higher value owing to the release of residual stress. Moreover, Nano-sized Al3 (Sc, Zr) precipitates on the grains boundaries hamper grain growth, which was responsible for the grain sizes maintaining after aging treatment. Graphical abstract: Unlabelled Image Highlights: The strength and ductility trade-off of the alloy can be tailored by regulating aging parameters. The diffraction peaks show the secondary peak of Al3 (Sc, Zr) after aging treatment owing to the precipitation particles. The segregation of Al3 (Sc, Zr) particles on grains boundaries was characterized.